The Impact of Regional Trade Agreements on Georgia's Exporters : A Firm-Level Analysis - Neri-Laine, Matteo; Orefice, Gianluca; Ruta, Michele (World Bank, Washington, DC, 2021)
This paper assesses the trade impact of regional trade agreements signed by Georgia. Using information from the World Bank’s Deep Trade Agreements database and the Exporters’ Dynamics Database for Georgia for 2000–20, the paper tests the effect of regional trade agreements on the performance of Georgian exporters. The results show that the depth of regional trade agreements has a positive effect on the exports of firms, and the more so if trade agreements include legally enforceable provisions. Interestingly, the effect of regional trade agreements is not homogeneous across exporters with different characteristics. While large exporters and firms participating in global value chains benefit from deep trade agreements, small firms are negatively affected. Deep trade agreements have a positive effect on the probability of entry into the export market for large firms and firms in global value chains.